Decadal Chlorophyll-a Dynamics and Trophic Status of Mahakam Delta Coastal Waters (2014–2024) - Romansah Wumu; Suparjo Suparjo; Karno Karno; Nia Kurniadin (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
Chlorophyll-a (Chl-a) is a key proxy for assessing phytoplankton biomass and trophic status of coastal waters. This study analyzes spatiotemporal Chl-a dynamics across three Areas of Interest (AOIs) in the Mahakam Delta coastal waters, East Kalimantan, Indonesia: Delta Mahakam (DM), Muara Badak-Marangkayu (MB), and Muara Jawa-Samboja (MJ). Monthly Chl-a data from the Copernicus Marine Ocean Color V6 (CMEMS) product were processed through Google Earth Engine from 2014 to 2024. DM recorded the highest mean Chl-a (5.30 ± 1.02 mg/m³), followed by MJ (3.01 ± 0.83 mg/m³) and MB (1.76 ± 0.60 mg/m³). Under OECD classification, DM was dominantly mesotrophic, MB oligotrophic, and MJ showed the only statistically significant increasing trend (R² = 0.518, p = 0.013). Chl-a peaked during the rainy season (October–March), driven by monsoonal riverine nutrient pulses. HYCOM surface currents confirmed that monsoon reversals modulate coastal phytoplankton distribution. These findings provide baseline data for coastal ecosystem monitoring and marine spatial planning in East Kalimantan.